Seni Rupa Pasemah: Arah Hadap dan Orientasi Karya Seni Rupa Pasemah - Suryanegara, A. Erwan; Sachari, Agus (PANGGUNG, 2016)
ABSTRACTÃÂ In Bukit Barisan of southern Sumatra, exactly in Lahat and Pagaralam, South Sumatra, was found remains of megalithic artifacts. The artifacts in the form ofvisual arts are in larger quantities, particu- larly sculptures other than paintings,reliefs, etc. Surveys and literature studies show that visual arts as those contemporary Pasemah visual arts are not yet discovered in other regions. One ofspecial charac- teristics is Point of the Orientation and the Orientation of sculptures which is not referring to point of the compass, rather to the object of nature surroundings. The Pasemah visual arts are never apart from the underlyingEcocentric concept and in harmony with the worship of ancestral souls in a cosmocentric mystical culture. The uniqueness of Pasemah visual arts is, actually, potential that must be excavated and prolif- erated as learning for citizens and, thus, inspire community surroundings in particular and Nusantara societies in general.ÃÂ Keywords: Pasemah, sculpture, megalithic, point, orientationÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ABSTRAKÃÂ Bukit Barisan bagian selatan Sumatra, tepatnya di Lahat dan Pagaralam, Sumatra Selatan, ditemukan peninggalan artefak-artefak megalitik. Secara kuantitatif memperlihatkan bahwa jumlah artefak berwujud karya seni rupa (visual) lebih banyak, terutama yang berbentuk pa- tung selain lukisan, relief, dan sebagainya. Kajian atas hasil survei dan studi literatur membuk- tikan bahwa seperti karya visual Pasemah itu memang tidak ditemukan di kawasan lain yang sezaman. Satu kekhasannya adalah Arah Hadap dan Orientasi patung yang tidak mengacu ke- pada arah mata angin, tetapi kepada objek alam di sekitarnya. Karya-karya visual Pasemah itu tidak pernah lepas dari konsep ekosentris yang menjadi konsep mendasar dan selaras dengan pemujaan arwah leluhur dalam peradaban mistis yang kosmosentris. Keunikan karya visual Pasemah sesungguhnya merupakan potensi yang harus digali dan ditumbuhkembangkan se- bagai pembelajaran bagi anak bangsa, sehingga dapat menginspirasi masyarakat sekitar khu- susnya maupun masyarakat Nusantara umumnya.ÃÂ Kata kunci: Pasemah, patung, megalitik, arah, orientasi